Influencing Factors of Health Technology Assessment to Orphan Drugs: Empirical Evidence in England, Scotland, Canada, and Australia - Na Zhou; Na Zhou; Hong Ji; Zheng Li; Jun Hu; Jia-Hua Xie; Yu-Heng Feng; Ni Yuan (Frontiers Media S.A., 2022)
This study summarizes the intrinsic criteria for the recommendation of orphan drugs in England, Scotland, Canada, and Australia with the aim of understanding the rationale for the variability in decision-making and to provide a reference for the establishment of criteria in the process of access to health insurance for orphan drugs in different countries and the construction of national uniform criteria. A comparative analysis of 60 health technology assessment (HTA) guidelines of 15 drug-indication pairs appraised by four countries (England, Scotland, Canada, and Australia) from 2017 to 2018 was done, including an in-depth analysis of a case study. Agreement levels were measured using kappa scores. Associations were explored through correspondence analysis. The four countries possess some homogeneity in the assessment, but each has its own preferences. Poor agreement exists between England, Scotland, and Canada (−0.41 < kappa score < 0.192). In the correspondence analysis, England placed more emphasis on treatment methods in terms of control type when making recommendations. Canada and Scotland focused more on trial type with Canada placing more emphasis on phase III and open-label trials and on cost-utility analysis, while Australia was less studied in terms of economic models. Different countries have different goals when establishing HTA decisions for orphan drugs due to their different degrees of orphan drug coverage. Different countries should not only combine their unique values of clinical benefit and cost-effectiveness in the assessment of orphan drugs but also give different weights during the HTA process, after considering account the development of the country itself.